Niveles de resiliencia y miedo al Covid-19 en personal médico. Hospital Provincial General Docente Riobamba, 2021 - Jiménez Velasco, Angélica Vaneza (2022)
The objective of this research was to evaluate the levels of resilience and fear of COVID-19 in the medical staff of the Hospital Provincial General Docente Riobamba, it corresponds to a non-experimental study of cross-sectional type and descriptive correlational level. Two psychological instruments were used: Wagnild and Young´s Resilience Scale (2002) and the COVID-19 Fear Scale created by Ahorsu and collaborators (2020). The population consisted of 491 resident physicians and attending staff. In the results obtained, it can be observed that 51,3 % present a high level of resilience, 26,7% a moderate level, 22% low levels of resilience, as for fear of COVID-19, 57,2% little fear, 27,7% moderate fear, followed by 15,1% a lot of fear. Spearman´s Rho test was applied, thus confirming the associating between the two study variables with p=0,00. Currently, fear of COVID-19 has been reduced due to the considerable decrease in serious cases and massive contagions in hospitals, increasing the resilient characteristics of health personnel.